Learning Arabic For Children With Special Needs - Mustofa, Muhamad Arif; Rini, Rini (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Learning Arabic for children with special needs challenges requires a flexible and creative approach. The complexity of grammar and the breadth of vocabulary are often additional hurdles for students with special needs. Therefore, it is essential to design teaching strategies tailored to students' characteristics and individual needs. This study reviews effective teaching methods like visual media, multisensory approaches, and personalized learning. Support from families and cooperation with education professionals are essential in creating an inclusive and supportive learning environment. This study uses a qualitative method to deeply understand the problems of Children with Special Needs learning Arabic. Data was collected through interviews, observations, documentation, and FGDs, then analyzed descriptively with an inductive approach through the stages of reference collection, data analysis, explanation of findings, and conclusion drawing. By understanding the specific needs of students, teachers can develop a comprehensive lesson plan. With innovation and dedication in teaching methods, it is hoped that every ABK student can achieve their best ability in learning Arabic. This research aims to offer insights and practical guidance for educators in overcoming existing challenges while improving the learning experience of students with special needs. Research shows that learning Arabic for Children with Special Needs needs an adaptive approach with the help of visual, audio, and interactive methods to improve understanding and motivation to learn.